Neonatal septicemia in a neonatal intensive care unit: results of four years - Samancı, Nedim; Ovalı, Fahri; Akdoğan, Zeliha; Dağoğlu, Türkan (The Turkish Journal of Pediatrics, 1997)
The outcome of congenital and nosocomial septicemia has been documented in infants who were admitted to a neonatal intensive care unit over a four-year period. The overall incidence of neonatal septicemia in the neonatal intensive care unit was 5.4 percent. Common causes of neonatal septicemia were gram-negative bacilli and staphylococci. Gram-positive microorganisms were the major causative agents for early-onset septicemia. Since the most common pathogen in cases of nosocomial sepsis was gram-negative bacillus, higher mortality rates were observed in nosocomial sepsis. The overall mortality rate in neonatal sepsis was 44.2 percent. The mortality rate in infants in whom nosocomial septicemia developed was significantly higher than in the infants in whom early-onset septicemia developed. However, as gram-negative colonization of the nursery recently changed to gram-positive microorganisms, the mortality rate is hoped to decrease.